ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN PERMASALAHAN OPERASI BENTUK ALJABAR - Malihatuddarojah, Dewi; Prahmana, Rully Charitas Indra (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2019)
Algebra is a very important subject in mathematics learning. Therefore, students especially at seventh-grade must be able to understand this concept well. This study aims to explore information and describe students’ errors in solving algebraic problems. The research method in this study uses qualitative descriptive. The subjects of this study were 36 seventh-grade students of SMP Muhammadiyah Kalasan. The instrument in this study is a test consisting of 10 questions about the operation of algebraic forms. The results showed that students still made some mistakes in solving algebraic problems, such as errors in the variable, errors in negative signs, errors in completing the form of algebraic equations, errors in the operation of the algebraic form, and errors in solving fractions.DOI : 10.22342/jpm.13.1.6668.1-8